THE COMPARATIVE ANALYSIS OF STUDENTS’ WRITING ABILITY BETWEEN RECOUNT TEXT AND DESCRIPTIVE TEXT AT SMAN 18 MAKASSAR - Dewi Astari Putry Utami; Hj Nurfaisah Sahib; Ulfah Syam (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2021)
This writing aims to analysis the difference between students’ ability in writing recount text and descriptive text at SMAN 18 Makassar (comparative analysis). The population of this writing was the tenth-grade students of SMAN 18 Makassar at the first semester 2021/2022 academic year. The writer took 270 students as population. The data were obtained from the writing text. The writer choose of class X IPA 3 and the writer took 30 students as a sample. The results of the writing used inferential analysis of t-test by SPSS v.16. It showed that there was a significant difference in the students’ mean score writing ability between recount text and descriptive text. The mean score of the students’ writing test recount text is 82.20 while descriptive text is 76.43. The significance value calculated 0.014 is smaller than 0.05 (P-value = 0.014 < 0.05). Therefore, the hypothesis of these writing was accepted. It means that, there were a Comparative difference of Students’ Writing Ability Between Recount Text and Descriptive Text at SMAN 18 Makassar. The writer concluded, that the students are easier to express ideas, understanding, composed and write a recount text than descriptive text. Based the results above, the writer can difference between students’ ability in writing recount text and descriptive text at SMAN 18 Makassar (comparative analysis).